A study on cathode structure and water transport in air-breathing PEM fuel cells - Jeong, Seong Uk; Cho, Eun Ae; Kim, Hyoung-Jhun; Lim, Tae-Hoon; Oh, In-Hwan; Kim, Sung Hyun (ELSEVIER, 2006)
For portable electronics, air-breathing PEMFCs are being developed without external air-feeding and humidification systems. To optimize the cathode structure and to investigate characteristics of such air-breathing PEMFCs, the effects of catalyst loading and gas diffusion layer (GDL) properties on the cell performance are examined. Water transport in air-breathing PEMFCs is interpreted in terms of the net water drag coefficient, which was obtained by changing the current density, relative humidity, temperature and the hydrogen stoichiometry to understand the water transport phenomena under various conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ELECTROOSMOTIC DRAG